(untitled) (Delta Medical College Journal, 2016)
The following retraction notice for this article appears in Vol.5(2) 2017 http://dx.doi.org/10.3329/dmcj.v5i2.33401 On 17th May 2017 the Editorial Board of Delta Medical College Journal agreed to retract the article Age Estimation from Ossification of Clavicle: A Comprehensive Review published in Delta Medical College Journal, Vol.4(2) pages 89-96 (DOI: http://dx.doi.org/10.3329/dmcj.v4i2.29381) as it was found to contain an extensive overlap of text sections from the following published article: Estimation of age from ossification of clavicle: A Comprehensive Review published in the Journal of Indian Academy of Forensic Medicine, Vol.31(3) pages 277-284. http://medind.nic.in/jal/t09/i3/jalt09i3p277.pdf Delta Med Col J. Jul 2016 4(2): 89-96